Antibiotic Resistance and Hly Plasmids in Serotypes of Escherichia coli Associated with Porcine Enteric Disease - Jørgensen, S. Tue (1976)
A total of 359 hemolytic Escherichia coli strains, representing eight pig pathogenic serotypes and isolated from pigs with enteric disease, was tested for transferable resistance to eight antibiotics. The co-transfer of plasmids controlling hemolysin production (Hly) with antibiotic resistance plasmids (R-factors) was evaluated. Transferable resistance to tetracycline, streptomycin, and/or sulfonamides was found in 47% of the total number of strains and 80% of the resistant ones. Chloramphenicol resistance was seldom seen. Co-transfer of Hly with R-factors occurred in 22.5% of the strains, generally to a degree excluding a genetic linkage. Stable coexistence of two R-factors in a cell was indicated by transfer patterns in 29 of the strains.